Economics of Acute Kidney Injury in the Critical Care Setting: Kidneys Need More Time and Money! - Reema Nair; Somu G; Srinivas Vinayak Shenoy; Laxmitha Shetty; Aparna Satish (Journal of Health Sciences and Surveillance System)
Background: Acute kidney injury (AKI) is a frequent complication among critically ill patients, contributing significantly to morbidity, mortality, and healthcare costs. Despite its impact, limited studies exist on the economic burden of AKI, particularly in the Indian healthcare context.Methods: From January to April 2021, we conducted a singlecenter, cross-sectional observational study at Kasturba Medical College, Manipal. The study included 132 patients directly admitted to the medical intensive care unit (ICU). Demographic and clinical data, including AKI etiology, healthcare costs, and insurance coverage, were collected and analyzed.Results: Of the 132 patients, 57.6% developed AKI, with sepsis identified as the leading cause (78%). Patients with AKI incurred significantly higher total healthcare costs (US$ 2452.4 vs. US$ 1556.8, P<0.001) and experienced longer ICU stays (8 days vs. 4 days, P<0.001) compared to those without AKI. Among AKI patients, 85.5% required hemodialysis. While 61% of patients had some form of health insurance, predominantly government-sponsored plans, coverage was limited, with a median reimbursement rate of 35.8%.Conclusion: AKI represents a substantial economic burden for critically ill patients, marked by higher costs and prolonged ICU stays. A deeper understanding of these financial implications is essential for guiding resource allocation and shaping healthcare policies to mitigate the economic impact of AKI.